The Adoption of Multiple Modes of Delivery in Australian Universities - Smith, A.; Ling, P.; Hill, D. (Journal of University Teaching and Learning Practice, 2006)
This paper reports the findings of a major nationalresearch project examining the use of multiplemodes of delivery in Australian universities. Avariety of factors including the increased use of onlineeducational technology has pushed Australianuniversities in recent years to extend the ways inwhich they deliver learning and teaching. However,the extent of the uptake of these modes of deliveryhas remained somewhat unclear as have theprecise reasons why universities have adoptedmultiple modes. The paper reports the result of asurvey which clarifies the extent of the use ofmultiple modes of delivery in Australian universitiesand case study research that attempts to unpackthe reasons for adoption. The research finds thattraditional face to face delivery is still the dominantform of delivery but universities are experimentingwith a surprisingly wide variety of alternatives.